Properties of Meromorphic Solutions of a Class of Second Order Linear Differential Equations - Benharrat Belaidi; Habib Habib (International Journal of Analysis and Applications, 2014)
This paper deals with the growth of meromorphic solutions of some second order linear differential equations, where it is assumed that the coefficients are meromorphic functions. Our results extend the previous results due to Chen and Shon, Xu and Zhang, Peng and Chen and others.